The NLRP1 inflammasome in skin diseases - Burian, Marc; Schmidt, Morna F.; Yazdi, Amir S. (Frontiers in Immunology, 2023)
Healthy human skin is constantly exposed to sterile and microbial agents. The skin immune system plays an important role in immune surveillance between tolerance and immune activation. This is mainly mediated by neutrophils, macrophages and most importantly lymphocytes. Keratinocytes, which form the outer skin barrier (epidermis) are also critical for cutaneous homeostasis. Being a non-professional immune cell, recognition of danger signals in keratinocytes is mediated by innate immune receptors (pattern recognition receptors, PRR). While Toll-like receptors are located on the cell membrane or the endosomes, nucleotide-binding domain and leucine-rich repeat containing gene family receptors (NLR) are intracellular PRRs. Some of these, once activated, trigger the formation of inflammasomes. Inflammasomes are multiprotein complexes and serve as platforms that mediate the release of innate cytokines after successful recognition, thereby attracting immune cells. Moreover, they mediate the pro-inflammatory cell death pyroptosis. Best characterized is the NLRP3 inflammasome. The function of inflammasomes differs significantly between different cell types (keratinocytes versus immune cells) and between different species (human versus mouse). In recent years, great progress has been made in deciphering the activation mechanisms. Dysregulation of inflammasomes can lead to diseases with varying degrees of severity. Here we focus on the structure, function, and associated pathologies of the NLRP1 inflammasome, which is the most relevant inflammasome in keratinocytes.